First documentation of a clinical multidrug-resistant Enterobacter chuandaensis ST2493 isolate co-harboring bla NDM-1 and two bla KPC-2 bearing plasmids - Ruyan Chen; Chenyu Li; Hao Xu; Ruishan Liu; Haoyu Ge; Jie Qiao; Yi Liu; Xiaojing Liu; Lei Fang; Yanhao Shen; Xiaobing Guo (Scientific Reports)
Abstract The increasing prevalence of carbapenem-resistant Enterobacter cloacae complex (CREC) poses great challenges to infection treatment in the clinical setting. In this study, we reported the emergence of carbapenemase in a rare species, Enterobacter chuandaensis, belonging to the Enterobacter cloacae complex (ECC). We elucidated the genetic characteristics of carbapenem-resistant isolate FAHZZU5885, co-harboring bla NDM−1 and bla KPC−2. Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and average nucleotide identity (ANI) analysis were used to identify E. chuandaensis. S1 nuclease pulsed-field gel electrophoresis (S1-PFGE) and Southern blotting were used to clarify the number and size of the plasmids in FAHZZU5885. Antimicrobial phenotypes were identified by antimicrobial susceptibility testing (AST), and the characteristics of the strain were examined with whole-genome sequencing (WGS). The conjugation experiment and stability assay were conducted to verify the transferability and stability of the plasmid carrying carbapenemase-encoding genes. E. chuandaensis FAHZZU5885 was isolated from a perianal swab of a patient admitted to the ICU. This strain simultaneously carried bla NDM−1 and two bla KPC−2 genes. FAHZZU5885 was resistant to most of the tested antibiotics except for amikacin, tigecycline, and colistin. Two bla KPC−2 were located separately on two different plasmids, the ~ 120 kb IncFIA-IncFII plasmid and the ~ 80 kb IncR plasmid. Both plasmids shared the conserved sequence klcA-korC-ISkpn6-bla KPC−2 -ISkpn27-tnpR-tnpA. The bla NDM−1-bearing plasmid had the potential to transfer and can remain stable after successive passages. In addition, the bla NDM−1 was carried on a ~ 80 kb IncFII plasmid with the conserved sequence ISAba125-bla NDM−1-ble-trpF-dsbD-cutA-groS-groL. In summary, this study marks the first report of the multidrug-resistant E. chuandaensis strain FAHZZU5885 harboring two bla KPC−2-bearing plasmids, indicating the potential for the further dissemination of carbapenemase-encoding genes in novel species. The findings contribute to enhancing our understanding of CREC strains, emphasizing the need for continued and comprehensive surveillance of this species.